2015
DOI: 10.1002/mnfr.201500272
|View full text |Cite
|
Sign up to set email alerts
|

The complex immunological and inflammatory network of adipose tissue in obesity

Abstract: A number of approaches have been utilized in the prevention, management, and treatment of obesity, including, surgery, medication, diet, exercise, and overall lifestyle changes. Despite these interventions, the prevalence of obesity and the various disorders related to it is growing. In obesity, there is a constant state of chronic low-grade inflammation which is characterized by activation and infiltration of pro-inflammatory immune cells and a dysregulated production of high levels of pro-inflammatory cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
0
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 137 publications
(184 reference statements)
6
128
0
10
Order By: Relevance
“…The inverse relationship between serum α-tocopherol with the inflammatory markers IL-6 and hs-CRP in our study has been observed other studies [30], including in patients with CVD or its risk factors [31]. Smoking and overweight are inflammatory states with higher levels of oxidative stress [18,19], and we observed that individuals with higher BMI and smokers had decreased serum α-tocopherol concentrations, reflecting findings [5,23,32]. However, increased α-tocopherol does not appear to be beneficial, as supplementation of 800 IU/day in healthy or overweight adults [33,34] did not result in a decrease in inflammatory markers and may be due to α-tocopherol acting as a pro-oxidant at high concentrations [11].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The inverse relationship between serum α-tocopherol with the inflammatory markers IL-6 and hs-CRP in our study has been observed other studies [30], including in patients with CVD or its risk factors [31]. Smoking and overweight are inflammatory states with higher levels of oxidative stress [18,19], and we observed that individuals with higher BMI and smokers had decreased serum α-tocopherol concentrations, reflecting findings [5,23,32]. However, increased α-tocopherol does not appear to be beneficial, as supplementation of 800 IU/day in healthy or overweight adults [33,34] did not result in a decrease in inflammatory markers and may be due to α-tocopherol acting as a pro-oxidant at high concentrations [11].…”
Section: Discussionsupporting
confidence: 71%
“…We also examined the relationship between tocopherol homologues and inflammatory markers and smoking and body mass index (BMI), two factors known to affect the inflammatory state [5,[18][19][20], hypothesizing that α-and γ-tocopherol would have opposing associations with BMD and the inflammatory states and markers.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is associated with immune function impairment, affecting both innate and adaptive immune systems (Andersen et al, 2016, Exley et al, 2014. Excess fat mass leads to systemic low-grade chronic inflammatory states, particularly active local inflammation in adipose tissue (Apostolopoulos et al, 2016). Chronic lowgrade inflammation is recognized as one of the key steps in pathogenesis of insulin resistance, type 2 diabetes mellitus, and atherosclerotic cardiovascular disease in obese individuals (Aarti et al, 2008, Emanuela F, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…As obesity is the main risk factor associated with high CRP and pro-inflammatory state in populations with metabolic syndrome or type-2 diabetes, an understanding of the immunological complexity in obesity is imperative (Fig. 1) [24][25][26][27].…”
mentioning
confidence: 99%